Cautery for lower lid entropion. - el-Kasaby, H T (1992)
A prospective study was undertaken to evaluate a simple cautery technique for the correction of involutional lower lid entropion in 50 patients. After a 12 month follow-up period all patients were free of entropion. Only one patient needed to have the procedure repeated because of recurrence. The technique was found to be simple, effective, safe, and required very little time and skill.